PERAN GANDA ISTRI NELAYAN PADA MASYARAKAT PESISIR DI DESA KIMA BAJO KECAMATAN WORI KABUPATEN MINAHASA UTARA - Torere, Wirdayanti; Goni, Shirley Y.V.I; Waani, Fonny J. (HOLISTIK, Journal Of Social and Culture, 2019)
Fishing households are one of the real examples of pre-prosperous families in the community. The fishermen's household has long been known to be poor, farmworker, and craftsmen. The poverty condition of fishermen is a complex problem as a result of the hellessness of fishermen against the access of natural resources available. The low education, skills, absence of capital and low accessibility cause fishermen to become increasingly marginalized Group.The fisherman's wife turned out to have an important role in solving and overcoming the natural poverty as an effort to improve the welfare of his household. The fishermen community in the village of Kima Bajo is one of the real evidence in the community about the double role of wives in fishing communities. As the wife not only exercised her role and responsibilities as a housewife but because her erratic husband's income required her wives to work in helping husbands to meet the needs of their families.For example, housewives are the ones that make crab catches, looking for crabs by using nets, and they sell them to nearby markets. In addition to utilizing the seafood there are also mothers who work as a laundry, selling cakes around, and even some who have had business food stalls, canteen business. With these works mothers find it helpful and the needs of their families can be fulfilled.Most of the wives of fishermen in the village of Kima Bajo have a side job, some have a stall business, sell cakes, canteen business, petrol sellers, washers/clothes irons, and also the maker of crab capture equipment (IGI). From this result the lack of income husbands can be covered.Keywords: fishermen, housewife, role